Court martial and military matters - Kumar, Brig Nilendra (New Delhi : Manas publication, 1999)
The book highlights topics such as recent changes made to military law, professional conduct of officers handling disciplinary cases, in-house remedies against court martial verdicts, futuristic trends in military law, alternative disputes redressal and human rights in countext of disposal of disciplinary cases in the army. Three chapters discuss various facets of international humanitarian law as relevant in Indian context. This work is an attempt to discuss the complexities of modern legal thought as pertaining to the military canvas. The book is thorough overview of military law. It is not however a treatise that merely describes the law. It point the way head. it is an agenda for change. The book will be of immense use as a reference work not only for students of military law but for commanders at all levels, research scholars, academicians and other interested in the study of military law.
Includes bibliographical references